Choice Between Non-Equity Entry Modes: An Organizational Capability Perspective - Krishna Erramilli, M.; Agarwal, Sanjeev; Dev, Chekitan S. (Journal of International Business Studies, 2002)
Many studies have examined the choice between different types of equity and non-equity modes; however, none has focused on the choice between different types of non-equity modes that service firms employ routinely. This study develops a theoretical framework based on the “organizational capability” perspective to explain the choice between two non-equity modes— franchising and management-service contracts. While previous studies are based on the premise that foreign market entrants choose a mode—equity or non-equity—that offers them most control given their particular circumstances, the premise of this study is that foreign entrants choose a non-equity mode that, in addition, offers effective transfer of the firm's capabilities to the host-country venture.